Temperature effects on the radiation damage morphology in nanocrystalline iron. (May 2022) - Vetterick, G.; Hung, C-Y.; Hopkins, E.; Balwin, J.K.; Baldo, P.; Kirk, M.A.; Misra, A.; He, S.; Marian, J.; Taheri, M.L.
Abstract: While transformations of dislocation-loop character at high temperatures during heavy ion irradiation has been studied for more than two decades, the role of grain size, or high sink density, has not been considered. To interrogate the effect of defect mobility on irradiated nanocrystalline (nc) microstructures at elevated temperatures, detailed in-situ ion irradiation transmission electron microscopy (TEM) studies were carried out. The transformation temperature for the Burgers vector b = 1/2 <111>-to-<100> transition was found to be 450 °C, representing a lower threshold than that found in micron-grain-sized counterparts. The formation of stable b = 1/2<111> dislocation loops is observed below 400 °C, while at 450∼500 °C, 1/2<111> loops either transformed into 〈100〉 loops or were absorbed at grain boundaries (GBs). Thus, the substantial absorption of point defects and dislocation loops by GBs over a range of temperatures characteristically changes the defect morphology from large finger-shaped observed in micron-sized grains to small circular shape loops in nc grains. Graphical abstract: Image, graphical abstract